(untitled) (Journal of Mathematical Study, 2021)
In this paper we study the non-relativistic and low Mach number limits of strong solutions to a full compressible MHD-P1 approximate model arising in radiation magnetohydrodynamics. We prove that, as the parameters go to zero, the solutions of the primitive system converge to that of the classical incompressible magnetohydrodynamic equations.